2021
DOI: 10.2147/copd.s338851
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Disease Management for Chronic Obstructive Pulmonary Disease in Primary Care, from the Controlled Trial to Clinical Program: A Cohort Study

Abstract: Purpose Integrated disease management (IDM) for COPD in primary care has been primarily investigated under clinical trial conditions. We previously published a randomized controlled trial (RCT) where the IDM intervention improved quality of life (QoL) and exacerbation-related outcomes. In this study, we assess the same IDM intervention in a real-world evaluation and identify patient characteristics associated with improved outcomes. Methods This historical cohort study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…Another important aspect for further research could also be the impact on HRQoL of improving cooperation and communication between specialists and GPs. Recent literature shows that multidisciplinary approaches such as integrated disease management can result in a clinically relevant improvement in disease-specific HRQoL [66].…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect for further research could also be the impact on HRQoL of improving cooperation and communication between specialists and GPs. Recent literature shows that multidisciplinary approaches such as integrated disease management can result in a clinically relevant improvement in disease-specific HRQoL [66].…”
Section: Discussionmentioning
confidence: 99%
“…17 Further evaluative studies of the Best Care COPD Programme supported real-world effectiveness, reporting that Best Care improved patient and provider experiences, and that it was cost-effective and dominant relative to the usual standard of care. [18][19][20][21][22][23] As with the majority of studies forming a large body of published literature on IDM, the quantitative evaluations were limited to 1 year of locally collected follow-up data. 13 Additionally, even for pulmonary rehabilitation, a gold-standard COPD IDM intervention, the long-term impacts are unproven.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Figure2An overview of the Best Care integrated disease management programme. Adapted from Table1: Ferrone et al17 and Figure1: Hussey et al20 CAT, COPD Assessment Test; COPD, chronic obstructive pulmonary disease; GOLD, Global initiative for Obstructive Lung Disease.…”
mentioning
confidence: 99%
“…Assessing outcomes over three years, a large study of the German IDM programme found participants had reduced mortality risk (hazard ratio: 0.89, 95% confidence interval [CI]: 0.84-0.94) and higher total costs (€553 per year). 31 IDM can improve quality of life; [28][29][30] a recent costeffectiveness analysis of IDM in Canadian primary care by Scarffe et al, found the programme dominated UC, with cost savings and higher quality-adjusted life years (QALYs) in the short-(1-year; within-trial) and long-term (30-years; model-based analysis). 58 Approximating the effect on severe exacerbation from the same RCT, 29 corresponding analyses from our study (Canada, Policy 2; RR: 0.40) corroborate this finding of improved health outcomes and cost savings and provide additional evidence on the impact at alternative uptake levels.…”
Section: Findings In the Context Of Existing Literaturementioning
confidence: 99%
“…They often include pharmacological and non-pharmacological interventions (eg, treatment review, smoking cessation counselling, telemonitoring, etc.). Pulmonary rehabilitation is a well-known form of IDM; the organisation of two primary care programmes from Canada 29 , 30 and Germany 31 is detailed in Table S1 . A recent meta-analysis of 52 studies found improvements in disease-specific quality of life, exercise capacity and respiratory-related hospital admissions for patients with IDM.…”
Section: Introductionmentioning
confidence: 99%